Reducing missing fracture clinic radiographs by entrusting them to patients. - Calder, Peter R. (2004)
BACKGROUND: Missing radiographs in fracture clinics may compromise fracture management and lead to inappropriate use of clerical resources. METHODS: We prospectively compared the number of missing radiographs in two hospitals over a period of two months. In hospital A the radiographs were retained and in hospital B they were entrusted to the patients. RESULTS: At the completion of the study, entrusting patients with their radiographs resulted in statistically less radiographs missing from the clinic.